2020
DOI: 10.1038/s41598-020-73956-7
|View full text |Cite
|
Sign up to set email alerts
|

Universality in spectral condensation

Abstract: Self-organization is the spontaneous formation of spatial, temporal, or spatiotemporal patterns in complex systems far from equilibrium. During such self-organization, energy distributed in a broadband of frequencies gets condensed into a dominant mode, analogous to a condensation phenomenon. We call this phenomenon spectral condensation and study its occurrence in fluid mechanical, optical and electronic systems. We define a set of spectral measures to quantify this condensation spanning several dynamical sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Recently, it was reported that the amplitude A of the dominant mode of oscillations increases and follows a universal scaling law A ∝ H −2.0±0.2 [15]. A spectral measure µ, which quantifies the sharpening of peaks in the power spectrum as the system dynamics approaches OI, has also been introduced and another universal scaling law A ∝ µ −0.66±0.10 [37,38] has been discovered. In both cases, the scaling exponents are invariant across aero-acoustic, thermoacoustic and aeroelastic systems.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that the amplitude A of the dominant mode of oscillations increases and follows a universal scaling law A ∝ H −2.0±0.2 [15]. A spectral measure µ, which quantifies the sharpening of peaks in the power spectrum as the system dynamics approaches OI, has also been introduced and another universal scaling law A ∝ µ −0.66±0.10 [37,38] has been discovered. In both cases, the scaling exponents are invariant across aero-acoustic, thermoacoustic and aeroelastic systems.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the transition to oscillatory instability via intermittency follows universal scaling behaviours across different turbulent fluid mechanical systems [45,46]. These scaling behaviours during the emergence of oscillatory instabilities are elaborated in Sect.…”
Section: Transitions In Turbulent Systemsmentioning
confidence: 91%
“…The transition from stable operating conditions to thermoacoustic instability is viewed as the emergence of ordered patterns from a disordered state. This transition is often accompanied by a phenomenon known as spectral condensation [46], which is the sharpening and the amplification of the peak corresponding to the dominant mode of oscillations in the power spectrum. During the transition, the energy distributed over a wide range of frequencies gets condensed into the dominant frequency of oscillations.…”
Section: Spectral Condensationmentioning
confidence: 99%
See 2 more Smart Citations